Computing ethics - Karrar, Abdelrahman; Dahbur, Kamal (New York : Nova Science Publishers, 2021)
"Ethics is an important basis for controlling and regulating human behavior in all areas of life, including but not limited to dealing with other people at work. This book covers ethical issues related to the field of information technology and computing, and discusses some of the ethical issues from the perspective of the Arabic and Islamic cultures. The book concentrates on understanding the legal, ethical, and societal issues related to the field of information technology and computing without indulging into the implications of these issues on other fields, such as music or painting copyrights. The book is well suited for undergraduate and graduate students in colleges and universities in the Middle East and Islamic world. The book also provides an excellent foundation in ethical, legal and cultural decision-making for current and future professionals, practitioners and managers in the field of computer science and information technology. The book covers many fundamental and contemporary topics, including: Ethical theories, philosophy, responsibility and code of ethics History of computing ethics and ethics for the computing professions Professional ethics in Islam Negative uses of computers and the Internet Privacy, anonymity and position of Islam on privacy Ethical issues related to software piracy and intellectual property Supporting and opposing Islamic views on intellectual copyright Ethical Issues related to globalization Ethicality of threats and violation to information security Hackers, vandals, spyware and network security risks"--
Includes bibliographical references (pages [133]-142) and index.
Keywords: Computer science -- Moral and ethical aspects; Information technology -- Moral and ethical aspects